What determines ethical behavior in public organizations: is it rules or leadership? - Downe, James; Morgan, Karen; Cowell, Richard (2016)
Leadership is widely seen as having an important role in fostering ethical conduct in organizations, but the ways in which the actions of leaders intersect with formal ethics regulation in shaping conduct have been little researched. This article examines this issue through a qualitative study of the operation of the "ethical framework" for English local government, which entailed all councils adopting a code of conduct to regulate the behavior of local politicians. Studying local government provides an opportunity to examine how personal and managerial factors combine to influence ethical conduct and to analyze the ways in which ethical leadership is exercised through multiple people in leadership roles (politicians and managers). The article finds that organizations that exhibit consistently good conduct have multiple leaders who demonstrate good conduct but also act to preempt the escalation of problems and thereby minimize the explicit use of ethics regulation. - Reproduced.
Keywords: Organizations; Leadership; Local government